Plastid Osmotic Stress Activates Cellular Stress Responses in Arabidopsis . Issue 1 (27th March 2014) - Wilson, Margaret E.; Basu, Meera R.; Bhaskara, Govinal Badiger; Verslues, Paul E.; Haswell, Elizabeth S.
Abstract : Organelles as intracellular osmosensors: Arabidopsis mutants unable to relieve plastid osmotic stress constitutively activate the same cellular responses as environmental osmotic stress . Abstract: Little is known about cytoplasmic osmoregulatory mechanisms in plants, and even less is understood about how the osmotic properties of the cytoplasm and organelles are coordinately regulated. We have previously shown that Arabidopsis ( Arabidopsis thaliana ) plants lacking functional versions of the plastid-localized mechanosensitive ion channels Mechanosensitive Channel of Small Conductance-Like2 (MSL2) and MSL3 contain leaf epidermal plastids under hypoosmotic stress, even during normal growth and development. Here, we use the msl2 msl3 mutant as a model to investigate the cellular response to constitutive plastid osmotic stress. Under unstressed conditions, msl2 msl3 seedlings exhibited several hallmarks of drought or environmental osmotic stress, including solute accumulation, elevated levels of the compatible osmolyte proline (Pro), and accumulation of the stress hormone abscisic acid (ABA). Furthermore, msl2 msl3 mutants expressed Pro and ABA metabolism genes in a pattern normally seen under drought or osmotic stress. Pro accumulation in the msl2 msl3 mutant was suppressed by conditions that reduce plastid osmotic stress or inhibition of ABA biosynthesis. Finally, treatment of unstressed msl2 msl3 plants with exogenous ABA elicited a much greater Pro accumulation response than in the wild type, similar to that observed in plants under drought or osmotic stress. These results suggest that osmotic imbalance across the plastid envelope can elicit a response similar to that elicited by osmotic imbalance across the plasma membrane and provide evidence for the integration of the osmotic state of an organelle into that of the cell in which it resides.